2021
DOI: 10.1016/j.ejca.2021.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Generating human prostate cancer organoids from leukapheresis enriched circulating tumour cells

Abstract: Background: Circulating tumour cell (CTC)ederived organoids have the potential to provide a powerful tool for personalised cancer therapy but are restrained by low CTC numbers provided by blood samples. Here, we used diagnostic leukapheresis (DLA) to enrich CTCs from patients with metastatic prostate cancer (mPCa) and explored whether organoids provide a platform for ex vivo treatment modelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 21 publications
0
52
0
Order By: Relevance
“…Measuring gene expression in single or a collection of pure CTCs (23) could give a more comprehensive and reliable sensitivity profile. Future research should also focus on diagnostic leukapheresis (DLA), since with this technique large amounts of CTCs can be obtained, and on generating organoids from CTCs to test drug sensitivity (24). Large amounts of patient derived and pure materials, in combination with techniques as single CTC genomics and transcriptomics, are promising tools to generate predictive sensitivity profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring gene expression in single or a collection of pure CTCs (23) could give a more comprehensive and reliable sensitivity profile. Future research should also focus on diagnostic leukapheresis (DLA), since with this technique large amounts of CTCs can be obtained, and on generating organoids from CTCs to test drug sensitivity (24). Large amounts of patient derived and pure materials, in combination with techniques as single CTC genomics and transcriptomics, are promising tools to generate predictive sensitivity profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been found that tumor cells may disseminate, even when the tumor is still "confined", or before the detection of the primary tumor by imaging [39,40]. Moreover, the assessment of living tumor cells has the advantage of directly measuring the response to treatment compared with evaluation after tissue fixation [41,42]. Notwithstanding the potential of CTCs, their use is limited by their scarcity and the need for highly specialized techniques enabling their isolation.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Indeed, following CTC isolation, several techniques can be used to investigate gene and protein expression [58]; genomic profiling can be carried out by sequencing; functional experiments can be conducted to evaluate metastasis, cell-cell communication, drug testing, and many other experiments [76] (Figure 1). Importantly, CTCs can be maintained in culture in vitro, either dissociated or as organoids, in which case they may be maintained for at least six weeks, as demonstrated by Mout et al [41]. Establishing PCa cell lines from liquid biopsy samples provides several advantages, including a lack of contaminant (and competing), normal epithelial and stromal cells, as well as the possibility of obtaining metastatic samples from patients with bone disease in a minimally invasive manner [41].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraging results from recent studies using patient-derived tumor organoids for personalized drug response profiling highlight the exceptional potential of these near-patient preclinical models in oncology research [ 5 , 6 , 7 , 8 ]. Additionally, in prostate cancer (PCa) research, organoids have been shown to be promising tools for preclinical drug testing and for studying emerging treatment resistant phenotypes [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%